HSV-2 Meningitis Disseminated from a Herpetic Whitlow - Karpathios, Themistocles; Moustaki, Maria; Yiallouros, Panayiotis K.; Sarifi, Fariba; Tzanakaki, Georgina; Fretzayas, Andrew M. (My University, 2013)
HSV-2 meningitis is uncommon in childhood and is mainly associated with genital lesions or a history of sexual abuse. A 7-year-old boy with recurrent herpetic whitlow developed HSV-2 meningitis. HSV-2 was identified in the CSF by PCR. In children with herpetic whitlow, the risk of HSV-2, although rare, should be considered.
Keywords: Herpetic whitlow; HSV-2; Meningitis; Mortality reduction efforts